First record of the genus Staurocladia (Hydrozoa: Cladonematidae) in the Gulf of Mexico with the description of Staurocladia dzilamensis sp. nov., a new species of crawling hydromedusa - Ahuatzin-Hernández, José María; Hernández-Solís, Pablo Alberto; León-Deniz, Lorena Violeta (European Journal of Taxonomy, 2024)
The Cladonematidae are a family of hydrozoans with a worldwide distribution and morphological adaptations for a benthic mode of life. Species of this family are characterized by high morphological variability, which has caused many taxonomical debates, mainly for the species of the genera Eleutheria Quatrefages, 1842 and Staurocladia Hartlaub, 1917. Herein, we describe Staurocladia dzilamensis sp. nov., a new species of crawling hydromedusa from the southern Gulf of Mexico. This finding also constitutes the first record of the genus Staurocladia for the Gulf of Mexico. The presence of additional nematocyst clusters, supplementing the apical one on the upper branch of the tentacles, places it within Staurocladia. The presence of exumbrellar buds, a conspicuous marginal ring of nematocysts, 6–11 bifid tentacles with lower branches longer than their upper counterpart, the cnidome with stenoteles of two size classes, and two nematocyst clusters on the upper branch supplementing the apical one, opposite placed alternately on its aboral and oral sides permits to differentiate S. dzilamensis from its congeners. A taxonomic key for the species of Staurocladia is provided.